Analysis of impact of meteorological conditions on human factors in estimating the risk of railway accidents - Aleksić, Dejan; Marković, Milan; Vasiljević, Marko; Stojić, Gordan; Pavlović, Norbert; Tanackov, Ilija (Transport, 2018)
This paper explores the accidents that occurred in the railway system of Serbian Railways from 2006 to 2012. The total number of the sample observed includes 3983 accidents, of which 2725 or 68.41% were caused by the human factor. One of the major contemporary problems – global climate change and the increase of average temperatures – has not yet been considered in the context of external factors for increasing the risk of accidents. The air pressure has become accepted as an external factor, in addition to the air temperature. It is assumed that temperature and air pressure have a significant impact on the risk of railway accidents occurrence (taking only accidents caused by a human factor into account). This assumption was made based on reduced cognitive abilities of railway staff as a result of extreme differences in temperature and air pressure. In this paper, the emphasis is put on Railway Crossings (RC) as sites where two forms of traffic intersect, since it is noticed that certain weather conditions have a significant effect on occurrence of accidents. The analysis of the observed sample of 266 accidents that occurred on RC shows that the risk of accident occurrence is significantly higher at low temperatures (from –10 to 0 °C) and high air pressures (p > 1010 mbar), the risk being 2.17, that is 2.41 times higher than in standard (average) weather conditions. Additionally, in the case of high temperatures (above 20 °C) and low air pressures (p < 1010 mbar) the risk rises to 2.07 in comparison to average weather conditions. The absolute risk of railway accident occurrence appears at temperatures below –10 °C and air pressures higher than 1010 mbar, as well as at high temperatures (T > 25 °C) and air pressures lower than 1010 mbar. First Published Online: 31 Aug 2017